2018
DOI: 10.1111/jgs.15456
|View full text |Cite
|
Sign up to set email alerts
|

Vision Impairment and Risk of Dementia: Findings from the English Longitudinal Study of Ageing

Abstract: Our study confirms and extends findings from other countries, demonstrating cross-sectional associations between moderate and poor self-rated vision and dementia in England in all participants aged 50 and older and longitudinally over an 11-year period in those aged 50 to 69. These results help establish vision loss as a risk factor for dementia, although it is unclear why. Research is needed to determine whether screening and treatment for vision loss may slow cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 40 publications
7
51
0
1
Order By: Relevance
“…However, there is some evidence suggesting that vision loss is associated with an increased risk of developing dementia diseases. Based on a retrospective cohort study that included 7,685 patients, Davies-Kershaw et al (2018) revealed that patients who rated their own vision as moderate were two times (HR 2.0, CI 95% 1.4-3.1) and those with very poor vision, which was comparable to being blind, four times (HR 4.0, CI 95% 2.6-6.1) more likely to have dementia compared to those without vision impairment. Furthermore, based on a population cohort of 7,736 initially healthy and non-dementia patients, Naël et al (2019) revealed that moderate to severe near-vision impairment was also associated with an increased risk of dementia in the first 4 years of follow-up (HR 2.0, CI 95% 1.2-3.3), but not when patients were followed for more than 4 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is some evidence suggesting that vision loss is associated with an increased risk of developing dementia diseases. Based on a retrospective cohort study that included 7,685 patients, Davies-Kershaw et al (2018) revealed that patients who rated their own vision as moderate were two times (HR 2.0, CI 95% 1.4-3.1) and those with very poor vision, which was comparable to being blind, four times (HR 4.0, CI 95% 2.6-6.1) more likely to have dementia compared to those without vision impairment. Furthermore, based on a population cohort of 7,736 initially healthy and non-dementia patients, Naël et al (2019) revealed that moderate to severe near-vision impairment was also associated with an increased risk of dementia in the first 4 years of follow-up (HR 2.0, CI 95% 1.2-3.3), but not when patients were followed for more than 4 years.…”
Section: Discussionmentioning
confidence: 99%
“…Neither refraction disorders nor severe visual impairment-including blindness-were found to be significantly associated with an increased risk of dementia diseases, which is contrary to some previous findings. The study of Davies-Kershaw et al (2018) was based on a large nationwide sample of people aged 50 years and older. However, just 2.5% (n = 195) of patients in the sample were diagnosed with dementia diseases, which is well below the general population estimates for a group of the same age composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual impairment [18], hearing loss [19], low gait speed [20], are few geriatric syndromes (GS), known to be risk factors for dementia as per previous literature. This study found a statistically significant association between urinary incontinence(p = 0.001) and MBI, mirroring the studies which showed an association between UI and depression [21] and anxiety [22].Urinary incontinence leads to distressing symptoms in older individuals [23] and is associated with dementia and frailty.…”
Section: Plos Onementioning
confidence: 99%
“…Poor vision and dementia are prevalent among older people, causing significant functional impairments, lower quality of life, and aggravation of comorbidities ( 1–5 ). Although poor vision has been postulated to increase risk of cognitive decline ( 6–14 ), longitudinal evidence of poor vision independently increasing risk of dementia is scarce ( 15 , 16 ). To date, only two longitudinal studies have examined the association between poor visual acuity and risk of dementia ( 17 , 18 ), and their results are conflicting.…”
mentioning
confidence: 99%